2020
DOI: 10.1007/978-3-030-64313-3_24
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot Navigation in the Wavelet Domain

Abstract: Many animals rely on robust visual navigation which can be explained by snapshot models, where an agent is assumed to store egocentric panoramic images and subsequently use them to recover a heading by comparing current views to the stored snapshots. Long-range route navigation can also be explained by such models, by storing multiple snapshots along a training route and comparing the current image to these. For such models, memory capacity and comparison time increase dramatically with route length, rendering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…To compensate for this, several image processing methods have been proposed. While some methods are similar to feature detection, as with skyline (Graham & Cheng, 2009), landmark (Möller et al, 1999) or Haar-like features (Baddeley et al, 2011), others take a holistic frequency filtering approach (Stone et al, 2018;Meyer et al, 2020). More computationally intensive methods like object recognition could be employed, albeit probably for simple shapes given low resolution insect vision.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for this, several image processing methods have been proposed. While some methods are similar to feature detection, as with skyline (Graham & Cheng, 2009), landmark (Möller et al, 1999) or Haar-like features (Baddeley et al, 2011), others take a holistic frequency filtering approach (Stone et al, 2018;Meyer et al, 2020). More computationally intensive methods like object recognition could be employed, albeit probably for simple shapes given low resolution insect vision.…”
Section: Discussionmentioning
confidence: 99%
“…We have not as yet exploited the multi-resolution aspect of our wavelet function since adding finer levels added computational burden. As discussed in [39], weighting coefficients at different scales could provide more scene recognition discriminability. In initial trials, we found that adding the higher resolution frequency bands tended to reduce the catchment area of reference images.…”
Section: Wavelet-based Image Matchingmentioning
confidence: 99%
“…In recent years, studies have shown that Haar like wavelet features can improve view discrimination in the task of visual homing while reducing memory requirements [31,39]. Here, we adopt a bandpass filtering approach, using a computational method that was originally inspired by the orientated bandpass filter properties of V1 neurons in vertebrates [48].…”
Section: Introductionmentioning
confidence: 99%